Resin composition, and prepreg, resin-coated film, resin-coated metal foil, metal-clad laminate, and wiring board using the same

By combining the modified polyphenylene ether compound and maleimide compound with low molecular weight styrene-butadiene copolymer, the problem of poor dielectric properties and moldability in printed circuit board materials is solved, and a multi-layer molding effect with high reliability and low defects is achieved.

JP7627865B2Active Publication Date: 2025-02-07PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021548815
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-27
Filing Date
2020-09-14
Publication Date
2025-02-07
Estimated Expiration
2040-09-14

AI Technical Summary

Technical Problem

When used in printed circuit board substrate materials, it is difficult for the existing resin composition to have low dielectric constant, low dielectric loss, good fluidity, heat resistance, high glass transition temperature, low water absorption and good adhesion. At the same time, defects such as voids are easily present during the multi-layer molding process, which affects the reliability of the connection.

Method used

A modified polyphenylene ether compound and a maleimide compound containing two or more N-substituted maleimide groups are used to combine a low molecular weight liquid styrene-butadiene copolymer to form a resin composition with a carbon-carbon unsaturated double bond. By controlling the molecular weight and the number of functional groups, the flowability and adhesion of the resin are improved, and fillers and initiators are added to improve moldability.

Benefits of technology

The resin composition with low dielectric constant, low dielectric loss, high heat resistance, low water absorption and good adhesion are achieved, which improves molding and handling properties, reduces defects in the multi-layer molding process, and enhances the reliability of the printed circuit board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627865000030
    Figure 0007627865000030
  • Figure 0007627865000031
    Figure 0007627865000031
  • Figure 0007627865000032
    Figure 0007627865000032
Patent Text Reader

Abstract

An aspect of the present invention relates to a resin composition comprising a modified poly(phenylene ether) compound having a carbon-carbon unsaturated double bond at an end of the molecule, a maleimide compound having two or more N-substituted maleimide groups in the molecule, and a liquid styrene / butadiene copolymer having a weight-average molecular weight less than 10,000 and having 1,2-vinyl groups.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, and to a prepreg, a resin-coated film, a resin-coated metal foil, a metal-clad laminate, and a wiring board each using the resin composition. [Background technology]

[0002] In recent years, with the increase in the amount of information processed by various electronic devices, mounting technologies such as higher integration of mounted semiconductor devices, higher density wiring, and multi-layering have rapidly advanced. Substrate materials constituting the base material of printed wiring boards used in various electronic devices are required to have low dielectric constants and dielectric loss tangents in order to increase the signal transmission speed and reduce loss during signal transmission.

[0003] Recently, it has been found that maleimide compounds are excellent in dielectric properties such as low dielectric constant and low dielectric loss tangent (hereinafter, also referred to as low dielectric properties). For example, Patent Document 1 reports that a curable resin composition containing a vinyl compound, a maleimide compound, and a styrene-based thermoplastic elastomer can provide a resin composition that has excellent curability even in the presence of oxygen and at low temperatures, in addition to properties such as a low relative dielectric constant and a low dielectric loss tangent. However, although it is believed that the dielectric properties can be improved by adding such a styrene-based thermoplastic elastomer having a large molecular weight compared to the case where it is not added, it is easily conceivable that the resin fluidity and moldability will be deteriorated accordingly.

[0004] When the above-mentioned resin composition is used as a molding material for a substrate material, the cured product is required to have not only excellent low dielectric properties but also a high glass transition temperature (Tg), heat resistance, and adhesion in order to obtain a laminate that shows high connection reliability over a wide temperature range. In addition, it is required to suppress moisture absorption into the substrate of the wiring board by reducing the water absorption of the cured product of the molding material so that the wiring board can be used even in a high humidity environment. Furthermore, there is a demand for improvements in moldability and handleability when the resin composition is made into a prepreg or film.

[0005] On the other hand, in recent years, as electronic devices have become smaller and thinner, surface mount packages have come to be used more frequently as electronic components in electronic devices. From the viewpoint of connection reliability and mounting reliability in these semiconductor packages, etc., there is a demand for substrate materials with a low thermal expansion coefficient to suppress substrate warpage.

[0006] In view of the above, the reality is that substrate materials for forming the substrate of wiring boards are required to have a high glass transition temperature, and to produce cured products that have excellent heat resistance and adhesion, low water absorption, a low coefficient of thermal expansion, and low dielectric properties, and are required to have excellent moldability and good handleability in prepregs, resin-coated films, resin-coated metal foils, and the like that contain the resin composition or a semi-cured product thereof. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 5649773 Summary of the Invention

[0008] The present invention has been made in view of the above circumstances, and aims to provide a resin composition that has excellent moldability and handleability in a prepreg, resin-attached film, resin-attached metal foil, laminate, etc., containing the resin composition or a semi-cured product thereof, and that has low dielectric properties, high heat resistance, high Tg, low coefficient of thermal expansion, adhesion, and low water absorption in a cured product of the resin composition. Another aim is to provide a prepreg, resin-attached film, resin-attached metal foil, metal-clad laminate, and wiring board using the resin composition.

[0009] A resin composition according to one embodiment of the present invention is characterized in that it contains a modified polyphenylene ether compound having a carbon-carbon unsaturated double bond at a molecular terminal, a maleimide compound having two or more N-substituted maleimide groups in one molecule, and a liquid styrene-butadiene copolymer having a weight average molecular weight of less than 10,000 and having a 1,2-vinyl group. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing the configuration of a prepreg according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing the configuration of a metal-clad laminate according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing the configuration of a wiring board according to one embodiment of the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view showing the structure of a resin-coated metal foil according to one embodiment of the present invention. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing the configuration of a resin film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] As described above, the resin composition according to the embodiment of the present invention is characterized by comprising a modified polyphenylene ether compound having a carbon-carbon unsaturated double bond at an end of the molecule, a maleimide compound having two or more N-substituted maleimide groups in one molecule, and a liquid styrene-butadiene copolymer having a weight average molecular weight of less than 10,000 and having a 1,2-vinyl group.

[0012] With this configuration, a resin composition can be provided that has excellent moldability and handleability in a prepreg, resin-attached film, resin-attached metal foil, etc., containing the resin composition or a semi-cured product thereof, and that has low dielectric properties, high heat resistance, a high glass transition temperature (Tg), a low coefficient of thermal expansion, adhesion, and low water absorption in a cured product of the resin composition. Furthermore, according to the present invention, by using the resin composition, a prepreg, resin-attached film, resin-attached metal foil, metal-clad laminate, and wiring board having the above-mentioned excellent properties can be provided.

[0013] Hereinafter, each component of the resin composition according to this embodiment will be specifically described.

[0014] (Modified polyphenylene ether compound) The modified polyphenylene ether compound used in the present embodiment is not particularly limited as long as it is a modified polyphenylene ether compound whose terminal is modified by a substituent having a carbon-carbon unsaturated double bond. It is considered that the inclusion of such a modified polyphenylene ether compound can provide both dielectric properties such as low dielectric constant and low dielectric loss tangent and high heat resistance.

[0015] Specific examples of the modified polyphenylene ether compound include modified polyphenylene ether compounds represented by the following formulas (1) and (2).

[0016] [ka]

[0017] [ka]

[0018] In the above formulas (1) and (2), R 1 ~R 8 and R 9 ~R 16 are independent of each other. That is, R 1 ~R 8and R 9 ~R 16 may be the same or different groups. 1 ~R 8 and R 9 ~R 16 represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group, among which a hydrogen atom and an alkyl group are preferred.

[0019] R 1 ~R 8 and R 9 ~R 16 Regarding the above, specific examples of the functional groups include the following:

[0020] The alkyl group is not particularly limited, but is preferably, for example, an alkyl group having 1 to 18 carbon atoms, and more preferably an alkyl group having 1 to 10 carbon atoms. Specific examples include a methyl group, an ethyl group, a propyl group, a hexyl group, and a decyl group.

[0021] The alkenyl group is not particularly limited, but is preferably an alkenyl group having 2 to 18 carbon atoms, and more preferably an alkenyl group having 2 to 10 carbon atoms. Specific examples include a vinyl group, an allyl group, and a 3-butenyl group.

[0022] The alkynyl group is not particularly limited, but is preferably an alkynyl group having 2 to 18 carbon atoms, and more preferably an alkynyl group having 2 to 10 carbon atoms. Specific examples include an ethynyl group and a prop-2-yn-1-yl group (propargyl group).

[0023] The alkylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkyl group, but is preferably an alkylcarbonyl group having 2 to 18 carbon atoms, and more preferably an alkylcarbonyl group having 2 to 10 carbon atoms. Specific examples include an acetyl group, a propionyl group, a butyryl group, an isobutyryl group, a pivaloyl group, a hexanoyl group, an octanoyl group, and a cyclohexylcarbonyl group.

[0024] The alkenylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkenyl group, but is preferably an alkenylcarbonyl group having 3 to 18 carbon atoms, and more preferably an alkenylcarbonyl group having 3 to 10 carbon atoms. Specific examples include an acryloyl group, a methacryloyl group, and a crotonoyl group.

[0025] The alkynylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkynyl group, but for example, an alkynylcarbonyl group having 3 to 18 carbon atoms is preferable, and an alkynylcarbonyl group having 3 to 10 carbon atoms is more preferable. Specific examples include a propioloyl group.

[0026] In the above formulas (1) and (2), A is a structure represented by the following formula (3), and B is a structure represented by the following formula (4), as described above:

[0027] [ka]

[0028] [ka]

[0029] In the formulas (3) and (4), the repeating units m and n each represent an integer of 1 to 50.

[0030] R 17 ~R 20 and R 21 ~R24 are independent of each other. That is, R 17 ~R 20 and R 21 ~R 24 may be the same group or different groups. 17 ~R 20 and R 21 ~R 24 is a hydrogen atom or an alkyl group.

[0031] Furthermore, in the above formula (2), Y may be a linear, branched or cyclic hydrocarbon having 20 or less carbon atoms. More specifically, Y may be, for example, a structure represented by the following formula (5):

[0032] [ka]

[0033] In formula (5), R 25 and R 26 are each independently a hydrogen atom or an alkyl group. Examples of the alkyl group include a methyl group. Examples of the group represented by formula (5) include a methylene group, a methylmethylene group, and a dimethylmethylene group.

[0034] In the above formulas (1) and (2), X 1 and X 2 are each preferably independently a substituent having a carbon-carbon unsaturated double bond represented by the following formula (6) or (7): 1 and X 2 may be the same or different.

[0035] [ka]

[0036] [ka]

[0037] In the above formula (6), a represents an integer of 0 to 10. In formula (7), when a is 0, it indicates that Z is directly bonded to the end of the polyphenylene ether.

[0038] In formula (6), Z represents an arylene group. The arylene group is not particularly limited. Specific examples include monocyclic aromatic groups such as phenylene groups, and polycyclic aromatic groups in which the aromatic ring is not monocyclic but is a polycyclic aromatic ring such as a naphthalene ring. The arylene group also includes derivatives in which a hydrogen atom bonded to the aromatic ring is substituted with a functional group such as an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group.

[0039] In addition, in formula (6), R 27 ~R 29 may be the same or different groups independently, and each represents a hydrogen atom or an alkyl group. The alkyl group is not particularly limited, and is preferably an alkyl group having 1 to 18 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms. Specific examples include a methyl group, an ethyl group, a propyl group, a hexyl group, and a decyl group.

[0040] A preferred specific example of the substituent represented by the above formula (6) is a functional group containing a vinylbenzyl group.

[0041] In the above formula (7), R 30 represents a hydrogen atom or an alkyl group. The alkyl group is not particularly limited, and is preferably, for example, an alkyl group having 1 to 18 carbon atoms, and more preferably an alkyl group having 1 to 10 carbon atoms. Specific examples include a methyl group, an ethyl group, a propyl group, a hexyl group, and a decyl group.

[0042] The substituent X in this embodiment 1 and X 2More specific examples of the alkyl group include vinylbenzyl groups (ethenylbenzyl groups) such as p-ethenylbenzyl group and m-ethenylbenzyl group, vinylphenyl groups, acrylate groups, and methacrylate groups.

[0043] It is believed that the use of the modified polyphenylene ether compounds represented by the above formulas (1) and (2) provides low dielectric properties such as low dielectric constant and low dielectric tangent, as well as excellent heat resistance, high Tg, and adhesion.

[0044] The modified polyphenylene ether compounds represented by the above formulas (1) and (2) can be used alone or in combination of two or more kinds.

[0045] In this embodiment, the weight average molecular weight (Mw) of the modified polyphenylene ether compound is not particularly limited, but is preferably 1000 to 5000, and more preferably 1000 to 4000. The weight average molecular weight may be measured by a general molecular weight measurement method, and specifically, may be a value measured using gel permeation chromatography (GPC). In addition, when the modified polyphenylene ether compound has repeating units (s, m, n) in the molecule, it is preferable that these repeating units have values ​​such that the weight average molecular weight of the modified polyphenylene ether compound falls within such a range.

[0046] When the weight average molecular weight of the modified polyphenylene ether compound is within such a range, it has the excellent low dielectric properties of polyphenylene ether, and not only is the heat resistance of the cured product excellent, but also the moldability is excellent. This is believed to be due to the following. When the weight average molecular weight of a normal polyphenylene ether is within such a range, it is a relatively low molecular weight, so the heat resistance of the cured product tends to decrease. In this respect, since the modified polyphenylene ether compound according to the present embodiment has an unsaturated double bond at the end, it has high reactivity, so it is believed that a cured product with sufficiently high heat resistance can be obtained. In addition, when the weight average molecular weight of the modified polyphenylene ether compound is within such a range, it is a relatively low molecular weight, so it is believed that the melt viscosity is low and the moldability is excellent. Therefore, it is believed that such a modified polyphenylene ether compound not only has excellent heat resistance of the cured product, but also has excellent moldability and appearance.

[0047] In addition, the average number of the substituents (number of terminal functional groups) at the molecular end per one molecule of the modified polyphenylene ether in the modified polyphenylene ether compound used in the present embodiment is not particularly limited. Specifically, it is preferably 1 to 5, more preferably 1 to 3. If the number of terminal functional groups is too small, Tg tends to decrease, and it is difficult to obtain a cured product with sufficient heat resistance. If the number of terminal functional groups is too large, the reactivity becomes too high, and there is a possibility that problems such as, for example, the storage stability of the resin composition decreases, or the flowability of the resin composition decreases due to an increase in melt viscosity may occur. That is, when such a modified polyphenylene ether is used, there is a possibility that a molding defect such as the generation of voids during multilayer molding may occur due to insufficient flowability, and a highly reliable printed wiring board may be difficult to obtain.

[0048] The number of terminal functional groups of the modified polyphenylene ether compound may be a numerical value representing the average value of the above-mentioned substituents per molecule of all modified polyphenylene ether compounds present in 1 mole of the modified polyphenylene ether compound. The number of terminal functional groups can be measured, for example, by measuring the number of hydroxyl groups remaining in the obtained modified polyphenylene ether compound and calculating the reduction from the number of hydroxyl groups of the polyphenylene ether before modification. The reduction from the number of hydroxyl groups of the polyphenylene ether before modification is the number of terminal functional groups. The number of hydroxyl groups remaining in the modified polyphenylene ether compound can be measured by adding a quaternary ammonium salt (tetraethylammonium hydroxide) that associates with hydroxyl groups to a solution of the modified polyphenylene ether compound and measuring the UV absorbance of the mixed solution.

[0049] In addition, the intrinsic viscosity of the modified polyphenylene ether compound used in the present embodiment is not particularly limited. Specifically, it may be 0.03 to 0.12 dl / g, but is preferably 0.04 to 0.11 dl / g, and more preferably 0.06 to 0.095 dl / g. If the intrinsic viscosity is too low, the molecular weight tends to be low, and low dielectric properties such as low dielectric constant and low dielectric loss tangent tend to be difficult to obtain. If the intrinsic viscosity is too high, the viscosity is high, sufficient fluidity cannot be obtained, and the moldability of the cured product tends to decrease. Therefore, if the intrinsic viscosity of the modified polyphenylene ether compound is within the above range, excellent heat resistance and moldability of the cured product can be realized.

[0050] The intrinsic viscosity here is the intrinsic viscosity measured in methylene chloride at 25° C., and more specifically, for example, the value measured by a viscometer using a 0.18 g / 45 ml methylene chloride solution (liquid temperature 25° C.) As the viscometer, for example, the AVS500 Visco System manufactured by Schott Corporation can be mentioned.

[0051] In addition, the method for synthesizing the modified polyphenylene ether compound preferably used in this embodiment is a method for synthesizing the modified polyphenylene ether compound using the above-mentioned substituent X 1 and X2 There is no particular limitation as long as a modified polyphenylene ether compound having a terminal modified by the above formula can be synthesized. Specifically, the modified polyphenylene ether can be synthesized by adding a substituent X 1 and X 2 and a method of reacting a compound having a halogen atom bonded thereto.

[0052] The raw material polyphenylene ether is not particularly limited as long as it can finally synthesize a predetermined modified polyphenylene ether. Specifically, polyphenylene ethers composed of 2,6-dimethylphenol and at least one of a bifunctional phenol and a trifunctional phenol, and poly(2,6-dimethyl-1,4-phenylene oxide) and the like, which are mainly composed of polyphenylene ether, can be mentioned. In addition, the bifunctional phenol is a phenolic compound having two phenolic hydroxyl groups in the molecule, for example, tetramethylbisphenol A, etc. In addition, the trifunctional phenol is a phenolic compound having three phenolic hydroxyl groups in the molecule.

[0053] As an example of a method for synthesizing a modified polyphenylene ether compound, for example, in the case of a modified polyphenylene ether compound represented by the above formula (2), specifically, the above polyphenylene ether and a substituent X 1 and X 2 Compounds in which a halogen atom is bonded (substituent X 1 and X 2 The compound having the substituent X is dissolved in a solvent and stirred. 1 and X 2 By reacting with a compound having the formula (2) of the present embodiment, the modified polyphenylene ether represented by the above formula (2) of the present embodiment is obtained.

[0054] In addition, this reaction is preferably carried out in the presence of an alkali metal hydroxide. It is believed that this allows the reaction to proceed favorably. This is believed to be because the alkali metal hydroxide functions as a dehydrohalogenation agent, specifically, a dehydrochlorination agent. That is, the alkali metal hydroxide eliminates hydrogen halide from the phenol group of the polyphenylene ether and the compound having the substituent X, and thereby the substituent X is substituted for the hydrogen atom of the phenol group of the polyphenylene ether. 1 and X 2 is thought to bind to the oxygen atom of the phenol group.

[0055] The alkali metal hydroxide is not particularly limited as long as it can act as a dehalogenating agent, and examples thereof include sodium hydroxide, etc. The alkali metal hydroxide is usually used in the form of an aqueous solution, specifically, an aqueous sodium hydroxide solution.

[0056] In addition, reaction conditions such as reaction time and reaction temperature are determined by the substituent X 1 and X 2 The reaction conditions vary depending on the compound having the formula (I) and are not particularly limited as long as the reaction proceeds favorably. Specifically, the reaction temperature is preferably from room temperature to 100° C., and more preferably from 30 to 100° C. The reaction time is preferably from 0.5 to 20 hours, and more preferably from 0.5 to 10 hours.

[0057] The solvent used in the reaction is polyphenylene ether and a compound having a substituent X 1 and X 2 and a compound having a substituent X 1 and X 2 There are no particular limitations on the type of solvent as long as it does not inhibit the reaction with a compound having the formula (I). Specific examples include toluene.

[0058] In addition, it is preferable that the above reaction is carried out in the presence of not only an alkali metal hydroxide but also a phase transfer catalyst. That is, it is preferable that the above reaction is carried out in the presence of an alkali metal hydroxide and a phase transfer catalyst. It is believed that the above reaction proceeds more favorably by doing so. This is believed to be due to the following. It is believed that the phase transfer catalyst is a catalyst that has the function of incorporating an alkali metal hydroxide, is soluble in both a polar solvent phase such as water and a non-polar solvent phase such as an organic solvent, and can move between these phases. Specifically, when an aqueous sodium hydroxide solution is used as the alkali metal hydroxide and an organic solvent such as toluene, which is not compatible with water, is used as the solvent, even if the aqueous sodium hydroxide solution is dropped into the solvent being used for the reaction, the solvent and the aqueous sodium hydroxide solution are separated, and it is believed that the sodium hydroxide is unlikely to move to the solvent. In that case, it is believed that the aqueous sodium hydroxide solution added as the alkali metal hydroxide is unlikely to contribute to promoting the reaction. On the other hand, when the reaction is carried out in the presence of an alkali metal hydroxide and a phase transfer catalyst, the alkali metal hydroxide is transferred to the solvent while being incorporated in the phase transfer catalyst, and the aqueous sodium hydroxide solution is likely to contribute to promoting the reaction. Therefore, when the reaction is carried out in the presence of an alkali metal hydroxide and a phase transfer catalyst, the reaction is believed to proceed more favorably.

[0059] The phase transfer catalyst is not particularly limited, but examples thereof include quaternary ammonium salts such as tetra-n-butylammonium bromide.

[0060] The resin composition according to the present embodiment preferably contains, as the modified polyphenylene ether, the modified polyphenylene ether obtained as described above.

[0061] (Maleimide compounds) Next, the maleimide compound used in this embodiment will be described. The maleimide compound used in this embodiment is not particularly limited as long as it is a maleimide compound having two or more N-substituted maleimide groups in one molecule. Such a maleimide compound reacts efficiently with the modified polyphenylene ether compound, so that high heat resistance can be obtained. In addition, the maleimide compound contributes to high Tg, low CTE (coefficient of thermal expansion), and low dielectric properties in the cured product of the resin composition.

[0062] Furthermore, the functional group equivalent of the maleimide group of the maleimide compound used in the present embodiment is not particularly limited, but is desirably 130 to 500 g / eq., more desirably 200 to 500 g / eq., and even more desirably 230 to 400 g / eq. If the functional group equivalent is within such a range, it is believed that the Tg of the cured product can be increased and the water absorption rate can be more reliably reduced.

[0063] The maleimide compound as described above is not particularly limited, but more specifically, preferred examples include the maleimide compounds represented by the following formulas (8) to (15). These may be used alone or in combination of two or more.

[0064] [ka]

[0065] In formula (8), the repeating unit t is an integer of 0.1 to 10.

[0066] [ka]

[0067] In formula (9), u, which is a repeating unit, is an average value and is greater than 1 and less than 5. 31 ~R 34 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, and a phenyl group.

[0068] [ka]

[0069] [ka]

[0070] [ka]

[0071] [ka]

[0072] [ka]

[0073] [ka]

[0074] As such a maleimide compound, commercially available products may be used, for example, BMI-4000, BMI-2300, BMI-TMH, etc. manufactured by Daiwa Kasei Kogyo Co., Ltd., MIR-3000, etc. manufactured by Nippon Kayaku Co., Ltd. may be used.

[0075] The content of the maleimide compound is preferably 5 to 50 parts by mass relative to 100 parts by mass of the total of the modified polyphenylene ether compound, the maleimide compound, and the styrene-butadiene copolymer. By including the maleimide compound in such a range, it is believed that a high Tg and a low water absorption rate can be more reliably achieved. More preferably, the content of the maleimide compound is 5 to 40 parts by mass, and even more preferably, 10 to 40 parts by mass.

[0076] (styrene-butadiene copolymer) Next, the liquid styrene-butadiene copolymer used in this embodiment, which has a weight average molecular weight of less than 10,000 and has a 1,2-vinyl group, will be described.

[0077] The styrene-butadiene copolymer of the present embodiment is not particularly limited as long as it has a weight average molecular weight of less than 10,000, has a 1,2-vinyl group, and is liquid.

[0078] Such a styrene-butadiene copolymer is hydrophobic and has few polar groups. Therefore, it is considered that adding it to the resin composition of the present embodiment can improve the low dielectric properties and reduce the water absorption rate. In addition, since the styrene-butadiene copolymer has a styrene skeleton, it can be appropriately mixed with the above-mentioned modified polyphenylene ether and maleimide compound to obtain a cured product without bleeding. Furthermore, since the styrene-butadiene copolymer has a butadiene skeleton which is an aliphatic skeleton, it reduces the elastic modulus of the cured product of the resin composition of the above-mentioned modified polyphenylene ether and maleimide compound, thereby suppressing the thermal expansion in the plane direction when made into a laminate, and thus exhibiting the excellent effect of reducing the warping of the substrate in a package substrate or the like.

[0079] The molecular weight is not particularly limited as long as it is less than 10,000 in weight average molecular weight, but from the viewpoint of solvent solubility, flowability, tackiness, heat resistance, etc., it is preferably 1,000 or more. A more preferable weight average molecular weight is 3,000 or more and less than 10,000. Since the molecular weight is low at less than 10,000, the styrene-butadiene copolymer of this embodiment has a low viscosity, and can improve the resin flowability and moldability when made into a resin composition. Furthermore, due to the relatively small molecular weight, it has a hydrophobic skeleton, but shows high solubility not only in nonpolar organic solvents such as toluene, but also in polar organic solvents such as methyl ethyl ketone. Therefore, it has the advantage that it is easily dissolved in various solvents when made into a resin composition, and when it is dissolved in a solvent to make a resin varnish, the varnish has excellent varnish stability. In the resin composition of this embodiment, a resin varnish can be easily prepared using the above-mentioned maleimide compound, which has a polar group and is therefore difficult to dissolve in nonpolar solvents, and methyl ethyl ketone, which is a polar solvent.

[0080] In this embodiment, the weight average molecular weight of the styrene-butadiene copolymer can be measured, for example, by absolute molecular weight measurement or gel permeation chromatography (GPC) using monodisperse polybutadiene as a standard substance.

[0081] In addition, since the styrene-butadiene copolymer of the present embodiment is liquid, the flexibility of the resin composition of the present embodiment is improved, and there is also the advantage that the handleability (reduction of powdering, etc.) of the resin composition when it is in a semi-cured state is improved.

[0082] In particular, it is preferable that the styrene-butadiene copolymer has a crosslinkable 1,2-vinyl group in the molecule, which makes it more reactive than a general styrene-butadiene polymer having many 1,4-bonds in the main chain. In addition, since the molecular weight is low, with a number average molecular weight of less than 10,000, it is believed that the reactivity of the 1,2-vinyl group in the styrene-butadiene copolymer is also higher. For these reasons, it is believed that the resin contributes to the curing reaction, and the appearance after molding is excellent without bleeding.

[0083] More specifically, for example, a styrene-butadiene copolymer having a structure shown in the following formula (16) can be mentioned.

[0084] [ka]

[0085] Formula (16) is an example of a styrene-butadiene copolymer that can be used in this embodiment, where x represents a 1,2 vinyl group, y represents a styrene group, and z represents a 1,4-bond.

[0086] Examples of structural units having a 1,2-vinyl group include the structural units shown below. Examples of structural units having a 1,4-bond include the structural unit shown in the following formula (II). Examples of styrene groups include the structural unit shown in the following formula (III).

[0087] [ka]

[0088] [ka]

[0089] [ka]

[0090] In this embodiment, the styrene-butadiene copolymer having a 1,2-vinyl group preferably has a repeating structure of the structural unit (I) and a repeating structure of the structural unit (III), and may further contain a repeating structure of the structural unit (II).

[0091] In the styrene-butadiene copolymer of the present embodiment, the styrene content in the molecule is preferably 50% by mass or less and the butadiene content is preferably 50% by mass or more, and more preferably the styrene content is 20 to 50% by mass and the butadiene content is 50 to 80% by mass. That is, the relationship between x, y, and z in the above formula (16) is as follows: y / (x+y+z)=20~50% (x+z) / (x+y+z)=50~80% It is preferable that the above-mentioned range of styrene content is satisfied. It is believed that the modified polyphenylene ether and the maleimide compound are mixed more reliably and a cured product without bleeding can be obtained, and a resin composition having a good balance of high Tg and adhesion can be obtained. In addition, it is believed that the above-mentioned range of butadiene content can reliably reduce the elastic modulus of the resin composition, and thus reduce the CTE in the plane direction when the resin composition is made into a laminate. If the CTE in the plane direction can be reduced, the warping of the substrate can be reduced in a package substrate or the like.

[0092] In this embodiment, the styrene and butadiene content in the styrene-butadiene copolymer can be measured, for example, by nuclear magnetic resonance spectroscopy (NMR).

[0093] Furthermore, in the styrene-butadiene copolymer of the present embodiment, the 1,2 vinyl content in the butadiene is preferably 30 to 70%. That is, the relationship between x and z in the above formula (16) is: x / (x+z)=30~70% It is considered that this contributes more to the curing reaction, and makes it possible to obtain a resin composition that is excellent in appearance after molding without bleeding of the resin.

[0094] In the present embodiment, the content of 1,2-vinyl groups in butadiene of the styrene-butadiene copolymer can be measured by, for example, infrared absorption spectroscopy (Morello method).

[0095] The styrene-butadiene copolymer of the present embodiment can be synthesized, for example, by copolymerizing a styrene monomer and a 1,3-butadiene monomer. Alternatively, commercially available products can be used, such as "Ricon 181", "Ricon 100" and "Ricon 184" manufactured by CRAY VALLEY.

[0096] The content of the styrene-butadiene copolymer is preferably 5 to 50 parts by mass relative to 100 parts by mass of the total of the modified polyphenylene ether compound, the maleimide compound, and the styrene-butadiene copolymer. By including the styrene-butadiene copolymer in such a range, it is believed that low dielectric properties, low thermal expansion coefficient, high moldability, and high adhesion can be more reliably achieved. More preferably, the content of the styrene-butadiene copolymer is 5 to 30 parts by mass, and even more preferably 5 to 20 parts by mass.

[0097] (Ratio of each component) In the resin composition of the present embodiment, the content ratio of the modified polyphenylene ether compound to the maleimide compound is 95:5 to 40:60 by mass ratio. If the content ratio of the modified polyphenylene ether compound is less than this range, the adhesion to the copper foil may be reduced. On the other hand, if the content ratio of the maleimide compound is less than this range, Tg may be reduced.

[0098] A more preferable content ratio range of the modified polyphenylene ether compound:the maleimide compound is 90:10 to 50:50.

[0099] (Other Ingredients) The resin composition according to the present embodiment may further contain other components in addition to the modified polyphenylene ether compound, the maleimide compound, and the styrene-butadiene copolymer.

[0100] For example, the resin composition according to the present embodiment may further contain a filler. Examples of the filler include those added to enhance the heat resistance and flame retardancy of the cured product of the resin composition, and are not particularly limited. In addition, by including a filler, the heat resistance and flame retardancy can be further enhanced. Specific examples of the filler include silica such as spherical silica, metal oxides such as alumina, titanium oxide, and mica, metal hydroxides such as aluminum hydroxide and magnesium hydroxide, talc, aluminum borate, barium sulfate, and calcium carbonate. Among these, silica, mica, and talc are preferable as the filler, and spherical silica is more preferable. In addition, the filler may be used alone or in combination of two or more types. In addition, the filler may be used as it is, or may be surface-treated with a silane coupling agent of epoxy silane type, vinyl silane type, methacryl silane type, or amino silane type. The silane coupling agent may be added to the filler by an integral blend method instead of a method of surface-treating the filler in advance.

[0101] Furthermore, when a filler is contained, the content thereof is preferably 10 to 200 parts by mass, and more preferably 30 to 150 parts by mass, per 100 parts by mass of the total of the organic components (the modified polyphenylene ether compound, the maleimide compound, and the styrene-butadiene copolymer).

[0102] Further, the resin composition of the present embodiment may contain a flame retardant, and examples of the flame retardant include halogen-based flame retardants such as bromine-based flame retardants and phosphorus-based flame retardants. Specific examples of the halogen-based flame retardant include bromine-based flame retardants such as pentabromodiphenyl ether, octabromodiphenyl ether, decabromodiphenyl ether, tetrabromobisphenol A, and hexabromocyclododecane, and chlorine-based flame retardants such as chlorinated paraffin. Specific examples of the phosphorus-based flame retardant include phosphate esters such as condensed phosphate esters and cyclic phosphate esters, phosphazene compounds such as cyclic phosphazene compounds, phosphinate-based flame retardants such as phosphinic acid metal salts such as dialkylphosphinic acid aluminum salts, melamine-based flame retardants such as melamine phosphate and polymelamine phosphate, and phosphine oxide compounds having a diphenylphosphine oxide group. As the flame retardant, each of the exemplified flame retardants may be used alone or in combination of two or more.

[0103] Furthermore, the resin composition according to the present embodiment may contain various additives other than those described above. Examples of the additives include antifoaming agents such as silicone-based antifoaming agents and acrylic acid ester-based antifoaming agents, heat stabilizers, antistatic agents, ultraviolet absorbers, dyes and pigments, lubricants, dispersants such as wetting dispersants, and the like.

[0104] The resin composition according to the present embodiment may further contain a reaction initiator. Although the curing reaction may proceed only with the modified polyphenylene ether compound, the maleimide compound, and the styrene-butadiene copolymer, depending on the process conditions, it may be difficult to raise the temperature to a level where the curing proceeds, so a reaction initiator may be added. The reaction initiator is not particularly limited as long as it can promote the curing reaction between the modified polyphenylene ether compound, the maleimide compound, and the styrene-butadiene copolymer. Specific examples of the reaction initiator include oxidizing agents such as α,α'-bis(t-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, benzoyl peroxide, 3,3',5,5'-tetramethyl-1,4-diphenoquinone, chloranil, 2,4,6-tri-t-butylphenoxyl, t-butylperoxyisopropyl monocarbonate, and azobisisobutyronitrile. In addition, a carboxylate metal salt or the like may be used in combination as necessary. By doing so, the curing reaction can be further accelerated. Among these, α,α'-bis(t-butylperoxy-m-isopropyl)benzene is preferably used. Since α,α'-bis(t-butylperoxy-m-isopropyl)benzene has a relatively high reaction initiation temperature, it can suppress the promotion of the curing reaction at the time when curing is not required, such as when drying the prepreg, and can suppress the deterioration of the storage stability of the resin composition. Furthermore, since α,α'-bis(t-butylperoxy-m-isopropyl)benzene has low volatility, it does not volatilize during drying or storage of the prepreg or film, and has good stability. In addition, the reaction initiator may be used alone or in combination of two or more kinds. As for the content, the reaction initiator is preferably used so that the addition amount is 0.1 to 2 parts by mass with respect to 100 parts by mass of the total of the modified polyphenylene ether compound, the maleimide compound, and the styrene-butadiene copolymer.

[0105] (Prepregs, resin-coated films, metal-clad laminates, wiring boards, and resin-coated metal foils) Next, the prepreg, metal-clad laminate, wiring board, and resin-coated metal foil using the resin composition of this embodiment will be described. In the following description, each reference numeral denotes: 1 prepreg, 2 resin composition or semi-cured resin composition, 3 fibrous base material, 11 metal-clad laminate, 12 insulating layer, 13 metal foil, 14 wiring, 21 wiring board, 31 resin-coated metal foil, 32, 42 resin layer, 41 resin-coated film, and 43 support film.

[0106] FIG. 1 is a schematic cross-sectional view showing an example of a prepreg 1 according to an embodiment of the present invention.

[0107] 1, the prepreg 1 according to this embodiment includes the resin composition or a semi-cured product of the resin composition 2, and a fibrous base material 3. An example of this prepreg 1 is one in which the fibrous base material 3 is present in the resin composition or a semi-cured product thereof 2. That is, this prepreg 1 includes the resin composition or a semi-cured product thereof, and the fibrous base material 3 present in the resin composition or a semi-cured product thereof 2.

[0108] In this embodiment, the term "semi-cured product" refers to a resin composition that has been partially cured to the extent that it can be further cured. In other words, the semi-cured product is a resin composition that has been semi-cured (B-staged). For example, when a resin composition is heated, the viscosity of the resin composition first gradually decreases, and then the resin composition begins to cure, and the viscosity gradually increases. In this case, the semi-cured product may refer to a state between when the viscosity starts to increase and when the resin composition is completely cured.

[0109] The prepreg obtained by using the resin composition according to the present embodiment may be a prepreg having a semi-cured product of the resin composition as described above, or may be a prepreg having the uncured resin composition itself. That is, the prepreg may be a prepreg having a semi-cured product of the resin composition (the resin composition in the B stage) and a fibrous base material, or a prepreg having the resin composition before curing (the resin composition in the A stage) and a fibrous base material. Specifically, for example, a prepreg having a fibrous base material in the resin composition may be mentioned. The resin composition or the semi-cured product thereof may be a prepreg obtained by heating and drying the resin composition.

[0110] The resin composition according to the present embodiment is often prepared in a varnish form and used as a resin varnish when producing the prepreg, or the resin-coated metal foil or metal-clad laminate described below. Such a resin varnish is prepared, for example, as follows.

[0111] First, each component that can be dissolved in an organic solvent, such as a modified polyphenylene ether compound, a maleimide compound, a styrene-butadiene copolymer, and a reaction initiator, is put into an organic solvent and dissolved. At this time, heating may be performed as necessary. Then, a component that is not dissolved in an organic solvent, such as an inorganic filler, is added, and the mixture is dispersed until a predetermined dispersion state is reached using a ball mill, a bead mill, a planetary mixer, a roll mill, or the like, to prepare a varnish-like resin composition. The organic solvent used here is not particularly limited as long as it dissolves the modified polyphenylene ether compound, the maleimide compound, and the styrene-butadiene copolymer, and does not inhibit the curing reaction. Specific examples include toluene, methyl ethyl ketone, cyclohexanone, and propylene glycol monomethyl ether acetate. These may be used alone or in combination of two or more.

[0112] The resin varnish of the present embodiment has the advantages of excellent storage stability, excellent film flexibility and film-forming properties, and excellent impregnation into glass cloth, and is easy to handle.

[0113] An example of a method for producing the prepreg 1 of this embodiment using the varnish-like resin composition of this embodiment is a method in which the fibrous base material 3 is impregnated with the resin composition 2 in the form of a resin varnish, and then dried.

[0114] Specific examples of the fibrous base material used in producing the prepreg include glass cloth, aramid cloth, polyester cloth, LCP (liquid crystal polymer) nonwoven fabric, glass nonwoven fabric, aramid nonwoven fabric, polyester nonwoven fabric, pulp paper, and linter paper. The use of glass cloth provides a laminate with excellent mechanical strength, and flattened glass cloth is particularly preferred. The glass cloth used in this embodiment is not particularly limited, and examples include low-dielectric glass cloths such as E glass, S glass, NE glass, Q glass, and L glass. Specifically, the flattening process can be performed by continuously pressing the glass cloth with a press roll at an appropriate pressure to compress the yarns flat. The thickness of the fibrous base material is, for example, 0.01 to 0.3 mm.

[0115] The resin varnish (resin composition 2) is impregnated into the fibrous substrate 3 by immersion, coating, etc. This impregnation can be repeated multiple times as necessary. In addition, it is also possible to repeat the impregnation using multiple resin varnishes with different compositions and concentrations, and to adjust the final composition (content ratio) and resin amount to the desired one.

[0116] The fibrous substrate 3 impregnated with the resin varnish (resin composition 2) is heated under desired heating conditions, for example, at 80° C. or higher and 180° C. or lower for 1 minute or longer and 10 minutes or shorter. By heating, the solvent is volatilized from the varnish, and the solvent is reduced or removed, thereby obtaining a prepreg 1 in an uncured (A stage) or semi-cured (B stage) state.

[0117] 4, the resin-coated metal foil 31 of this embodiment has a configuration in which a resin layer 32 containing the above-mentioned resin composition or a semi-cured product of the resin composition is laminated with a metal foil 13. That is, the resin-coated metal foil of this embodiment may be a resin-coated metal foil comprising a resin layer containing the resin composition before curing (the resin composition in A stage) and a metal foil, or a resin-coated metal foil comprising a resin layer containing a semi-cured product of the resin composition (the resin composition in B stage) and a metal foil.

[0118] Examples of a method for producing such a resin-coated metal foil 31 include a method in which the above-mentioned resin composition in the form of a resin varnish is applied to the surface of a metal foil 13 such as a copper foil, and then dried. Examples of the application method include a bar coater, a comma coater, a die coater, a roll coater, a gravure coater, and the like.

[0119] As the metal foil 13, any metal foil that is used in metal-clad laminates, wiring boards, etc. can be used without any limitations, and examples thereof include copper foil and aluminum foil.

[0120] 5, the resin-attached film 41 of this embodiment has a configuration in which a resin layer 42 containing the above-mentioned resin composition or a semi-cured product of the resin composition is laminated with a film support substrate 43. That is, the resin-attached film of this embodiment may be a resin-attached film comprising the resin composition before curing (the resin composition in A stage) and a film support substrate, or may be a resin-attached film comprising a semi-cured product of the resin composition (the resin composition in B stage) and a film support substrate.

[0121] As a method for producing such a resin-coated film 41, for example, a resin composition in the form of a resin varnish as described above is applied to the surface of the film support substrate 43, and then the solvent is volatilized from the varnish to reduce the solvent or remove the solvent, thereby obtaining a resin-coated film in an uncured (A stage) or semi-cured state (B stage) state.

[0122] Examples of the film support substrate include electrically insulating films such as polyimide films, PET (polyethylene terephthalate) films, polyester films, polyparabanic acid films, polyether ether ketone films, polyphenylene sulfide films, aramid films, polycarbonate films, and polyarylate films.

[0123] In the resin-coated film and resin-coated metal foil of this embodiment, similarly to the prepreg described above, the resin composition or a semi-cured product thereof may be obtained by drying or heating the resin composition.

[0124] The thickness of the metal foil 13 and the film support substrate 43 can be appropriately set according to the desired purpose. For example, the metal foil 13 can be about 0.2 to 70 μm. When the thickness of the metal foil is, for example, 10 μm or less, the metal foil may be a carrier-attached copper foil having a release layer and a carrier to improve handling. The resin varnish is applied to the metal foil 13 and the film support substrate 43 by coating or the like, which can be repeated multiple times as necessary. In addition, at this time, it is also possible to repeatedly apply multiple resin varnishes with different compositions and concentrations, and adjust the composition (content ratio) and resin amount to the final desired one.

[0125] There are no particular limitations on the drying or heating and drying conditions in the manufacturing method of the resin-coated metal foil 31 or the resin film 41, but after applying a resin varnish-like resin composition to the metal foil 13 or the film support substrate 43, it is heated under the desired heating conditions, for example, at 80 to 170°C for about 1 to 10 minutes to volatilize the solvent from the varnish and reduce or remove the solvent, thereby obtaining the resin-coated metal foil 31 or the resin film 41 in an uncured (A stage) or semi-cured (B stage) state.

[0126] The resin-coated metal foil 31 and the resin film 41 may be provided with a cover film or the like as necessary. By providing a cover film, it is possible to prevent the inclusion of foreign matter, etc. The cover film is not particularly limited as long as it can be peeled off without damaging the shape of the resin composition, but for example, a polyolefin film, a polyester film, a TPX film, a film formed by providing a release agent layer on these films, and further a paper in which these films are laminated on a paper base material can be used.

[0127] 2, the metal-clad laminate 11 of this embodiment is characterized by having an insulating layer 12 containing the cured product of the above-mentioned resin composition or the cured product of the above-mentioned prepreg, and a metal foil 13. Note that the metal foil 13 used in the metal-clad laminate 11 may be the same as the metal foil 13 described above.

[0128] The metal-clad laminate 11 of this embodiment can also be produced using the resin-coated metal foil 31 or resin film 41 described above.

[0129] A method for producing a metal-clad laminate using the prepreg 1, resin-coated metal foil 31, or resin film 41 obtained as described above is to produce a double-sided or single-sided metal foil laminate by stacking one or more prepregs 1, resin-coated metal foil 31, or resin film 41, stacking a metal foil 13 such as copper foil on both sides or one side of the prepreg 1, and heat-pressing and laminating the stack. Heat-pressing conditions can be appropriately set depending on the thickness of the laminate to be produced and the type of resin composition, but for example, the temperature can be 170 to 220°C, the pressure can be 1.5 to 5.0 MPa, and the time can be 60 to 150 minutes.

[0130] Alternatively, the metal-clad laminate 11 may be produced by forming a film-like resin composition on the metal foil 13 and applying heat and pressure thereto, without using the prepreg 1 or the like.

[0131] As shown in FIG. 3, wiring board 21 of this embodiment has insulating layer 12 containing the cured product of the above-mentioned resin composition or the cured product of the above-mentioned prepreg, and wiring 14.

[0132] The resin composition of the present embodiment is preferably used as a material for an interlayer insulating layer of a wiring board. Although not particularly limited, it is preferably used as a material for an interlayer insulating layer of a multilayer wiring board having 10 or more circuit layers, and further 15 or more circuit layers.

[0133] In addition, as the material of the interlayer insulating layer, it is preferable to use multiple layers of insulating layers made of the resin composition of this embodiment. Although not particularly limited, it is preferable to use, for example, 10 layers or more. This makes it possible to further increase the density of the conductor circuit pattern in the multilayer wiring board, and it is considered that the lower dielectric properties of the multiple interlayer insulating layers, the insulation reliability between the conductor circuit patterns, and the insulation between the interlayer circuits can be further improved. Furthermore, it is also possible to obtain effects such as increasing the signal transmission speed in the multilayer wiring board and reducing the loss during signal transmission.

[0134] As a method for producing such a wiring board 21, for example, the metal foil 13 on the surface of the metal clad laminate 13 obtained above can be etched or otherwise processed to form a circuit (wiring), thereby obtaining a wiring board 21 having a conductor pattern (wiring 14) provided as a circuit on the surface of the laminate. In addition to the above-mentioned methods, examples of the method for forming a circuit include circuit formation by a semi-additive process (SAP) or a modified semi-additive process (MSAP).

[0135] The prepreg, resin-coated film, and resin-coated metal foil obtained using the resin composition of this embodiment have good moldability and handleability, as well as low dielectric properties, low thermal expansion coefficient, high Tg, adhesion, and low water absorption in the cured product, making them very useful for industrial use. Furthermore, the metal-clad laminates and wiring boards obtained by curing them have high heat resistance, high Tg, low thermal expansion coefficient, high adhesion, low water absorption, and good appearance.

[0136] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples. EXAMPLES

[0137] First, the components used in preparing the resin composition in this example will be described.

[0138] <Modified polyphenylene ether compound> OPE-2St 1200: Terminal vinylbenzyl modified PPE (Mw: 1600, Mn 1200, manufactured by Mitsubishi Gas Chemical Co., Ltd.) OPE-2St 2200: Terminal vinylbenzyl modified PPE (Mw: 3600, Mn: 2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.)

[0139] Modified PPE-1: Bifunctional vinylbenzyl modified PPE (Mw: 1900) First, modified polyphenylene ether (modified PPE-1) was synthesized. The average number of phenolic hydroxyl groups at the molecular terminals per molecule of polyphenylene ether is referred to as the number of terminal hydroxyl groups.

[0140] Polyphenylene ether and chloromethylstyrene were reacted to obtain modified polyphenylene ether 1 (modified PPE-1). Specifically, first, 200 g of polyphenylene ether (SA90 manufactured by SABIC Innovative Plastics, intrinsic viscosity (IV) 0.083 dl / g, number of terminal hydroxyl groups 1.9, weight molecular weight Mw 1700), 30 g of a mixture of p-chloromethylstyrene and m-chloromethylstyrene in a mass ratio of 50:50 (chloromethylstyrene: CMS manufactured by Tokyo Chemical Industry Co., Ltd.), 1.227 g of tetra-n-butylammonium bromide as a phase transfer catalyst, and 400 g of toluene were charged into a 1-liter three-neck flask equipped with a temperature controller, a stirrer, a cooling device, and a dropping funnel, and stirred. Then, polyphenylene ether, chloromethylstyrene, and tetra-n-butylammonium bromide were stirred until they were dissolved in toluene. At that time, the mixture was gradually heated until the liquid temperature finally reached 75°C. Then, an aqueous solution of sodium hydroxide (20 g sodium hydroxide / 20 g water) was added dropwise to the solution as an alkali metal hydroxide over a period of 20 minutes. After that, the solution was further stirred at 75°C for 4 hours. Next, the contents of the flask were neutralized with 10% by mass of hydrochloric acid, and then a large amount of methanol was added. By doing so, a precipitate was generated in the liquid in the flask. In other words, the product contained in the reaction liquid in the flask was reprecipitated. Then, the precipitate was taken out by filtration, washed three times with a mixed liquid of methanol and water in a mass ratio of 80:20, and then dried under reduced pressure at 80°C for 3 hours.

[0141] The obtained solid is 1 The solid was analyzed by H-NMR (400 MHz, CDCl3, TMS). As a result of NMR measurement, a peak derived from ethenylbenzyl was confirmed at 5 to 7 ppm. This confirmed that the obtained solid was polyphenylene ether ethenylbenzyl-modified at the molecular terminal.

[0142] The molecular weight distribution of the modified polyphenylene ether was measured by GPC, and the weight average molecular weight (Mw) was calculated from the molecular weight distribution, and was found to be 1,900.

[0143] The number of terminal functionalities of the modified polyphenylene ether was measured as follows.

[0144] First, the modified polyphenylene ether was accurately weighed. The weight was designated as X (mg). The weighed modified polyphenylene ether was dissolved in 25 mL of methylene chloride, and 100 μL of a 10 mass% tetraethylammonium hydroxide (TEAH) ethanol solution (TEAH:ethanol (volume ratio) = 15:85) was added to the solution, and then the absorbance (Abs) at 318 nm was measured using a UV spectrophotometer (UV-1600 manufactured by Shimadzu Corporation). From the measurement results, the number of terminal hydroxyl groups of the modified polyphenylene ether was calculated using the following formula.

[0145] Residual OH amount (μmol / g) = [(25×Abs) / (ε×OPL×X)]×106 Here, ε is the extinction coefficient, 4700 L / mol cm, and OPL is the cell path length, 1 cm.

[0146] The calculated residual OH amount (number of terminal hydroxyl groups) of the modified polyphenylene ether was almost zero, which indicated that the hydroxyl groups of the polyphenylene ether before modification were almost all modified. This indicated that the decrease from the number of terminal hydroxyl groups of the polyphenylene ether before modification was the number of terminal hydroxyl groups of the polyphenylene ether before modification. In other words, it was found that the number of terminal hydroxyl groups of the polyphenylene ether before modification was the number of terminal functional groups of the modified polyphenylene ether. In other words, the number of terminal functional groups was 1.8. This is referred to as "modified PPE-1".

[0147] SA-9000: Bifunctional methacrylate modified PPE (Mw: 2000, manufactured by SABIC) SA90: Unmodified PPE (Mw: 1700, manufactured by SABIC Innovative Plastics)

[0148] <Maleimide compounds> MIR-3000: The above formula ( 9 ) (maleimide functional equivalent: 275 g / eq., manufactured by Nippon Kayaku Co., Ltd.) BMI-4000: Maleimide compound represented by the above formula (10) (maleimide functional group equivalent: 285 g / eq., manufactured by Daiwa Chemical Industry Co., Ltd.) BMI-5100: Maleimide compound represented by the above formula (14) (maleimide functional group equivalent: 222 g / eq., manufactured by Daiwa Chemical Industry Co., Ltd.) BMI-2300: Maleimide compound represented by the above formula (8) (maleimide functional group equivalent: 180 g / eq., manufactured by Daiwa Chemical Industry Co., Ltd.) BMI-TMH: Maleimide compound represented by the above formula (11) (functional group equivalent of maleimide group: 159 g / eq., manufactured by Daiwa Chemical Industry Co., Ltd.)

[0149] <Styrene-butadiene copolymer> Ricon 181: Styrene-butadiene copolymer (CRAY VALLEY, styrene: 28% by weight, butadiene: 72% by weight; 1,2 vinyl in butadiene: 30%; Mw approx. 5400) Ricon 100: Styrene-butadiene copolymer (manufactured by CRAY VALLEY, styrene: 25% by mass, butadiene: 75% by mass; 1,2 vinyl in butadiene: 70%; Mw approx. 6500) Ricon 184: Styrene-butadiene copolymer (CRAY VALLEY, styrene: 28% by weight, butadiene: 72% by weight; 1,2 vinyl in butadiene: 30%; Mw approx. 9800) Septon V9827: Hydrogenated SBS (styrene-butadiene-styrene) copolymer (Mw: 94,000, manufactured by Kuraray Co., Ltd.)

[0150] SX-100: Styrene-based polymer (Mw2500, manufactured by Yasuhara Chemical Co., Ltd.)

[0151] The weight average molecular weights of Ricon 181, Ricon 100, and Ricon 184 were measured by GPC (apparatus: HLC-8120GPC manufactured by Tosoh Corporation, columns: two Super HM-H columns manufactured by Tosoh Corporation, eluent: chloroform, standard sample: monodisperse polybutadiene manufactured by SAS).

[0152] <Other ingredients> (Reaction initiator) Perbutyl P: 1,3-bis(butylperoxyisopropyl)benzene (manufactured by Nippon Oil & Fats Co., Ltd.) (Inorganic filler) SC2500-SXJ: Phenylaminosilane surface-treated spherical silica (manufactured by Admatechs Co., Ltd.)

[0153] <Examples 1 to 23 and Comparative Examples 1 to 7> [Preparation method] (Resin varnish) First, modified PPE (or unmodified PPE), maleimide compound, and styrene-butadiene copolymer (or styrene-based polymer) were added to methyl ethyl ketone (MEK) in the mixing ratios shown in Tables 1 to 3 so that the solid content concentration was 40% by mass, and the mixture was heated and stirred at 70°C for 60 minutes to mix and dissolve. The mixture was allowed to cool to 25°C, and then peroxide and inorganic filler were added, stirred, and dispersed with a bead mill to obtain a resin varnish (MEK solution resin varnish). However, in Comparative Examples 4 and 5, an attempt was made to prepare a resin varnish by mixing each of the organic components with methyl ethyl ketone, but the styrene-based polymer did not dissolve, and an MEK solution resin varnish could not be prepared.

[0154] For Comparative Example 5, a resin varnish was prepared by the following method. The modified PPE and maleimide compound were added to MEK in the ratios shown in Table 2 so that the solid content concentration was 40% by mass, and the mixture was heated and stirred at 70°C for 60 minutes to mix and dissolve. A predetermined amount of a toluene solution of a styrene-based polymer adjusted to a solid content of 20% by mass was added thereto, and the mixture was allowed to cool to 25°C while being mixed and stirred. Thereafter, a peroxide and an inorganic filler were added, and the mixture was stirred and dispersed with a bead mill to obtain a resin varnish (MEK-toluene mixed solution resin varnish).

[0155] It should be noted that, for Comparative Example 4, a resin varnish could not be produced by this method either, and therefore, the following evaluation tests could not be carried out for the resin composition of Comparative Example 4.

[0156] (Prepreg) -Preparation of Prepreg I The resin varnishes of the respective Examples and Comparative Examples prepared above were impregnated into glass cloth (manufactured by Nitto Boseki Co., Ltd., #2116 type, E glass), and then heated and dried for about 4 minutes at 140° C. to obtain a prepreg. At that time, the content of the resin composition relative to the weight of the prepreg (resin content) was adjusted to be about 46% by mass.

[0157] ·Preparation of Prepreg-II The resin varnish of each Example and Comparative Example was impregnated into glass cloth (manufactured by Nitto Boseki Co., Ltd., #1067 type, NE glass), and then heated and dried at 140° C. for about 4 minutes to obtain a prepreg. At that time, the content of the resin composition relative to the weight of the prepreg (resin content) was adjusted to be about 73 mass%.

[0158] (Copper-clad laminate) One of the prepregs I was placed on both sides of a 12 μm thick copper foil (GT-MP manufactured by Furukawa Electric Co., Ltd.) to form a pressure body, and was then subjected to vacuum testing at a temperature of 220°C and a pressure of 40 kgf / cm. 2The laminate was heated and pressed for 90 minutes under the above conditions, with copper foil attached to both sides, to obtain a copper-clad laminate I having a thickness of about 0.1 mm. Eight sheets of the above prepreg were stacked together in the same manner to obtain a copper-clad laminate II having a thickness of about 0.8 mm.

[0159] Further, 12 sheets of the prepreg II were stacked together and subjected to the same method to obtain a copper-clad laminate III having a thickness of about 0.8 mm.

[0160] <Evaluation test> (Resin varnish storage stability) The MEK solution resin varnishes (Examples 1 to 23 and Comparative Examples 1 to 3, 6 to 7) and the MEK-toluene mixed solution resin varnish (Comparative Example 5) prepared above were allowed to stand at 25 degrees for 24 hours. If there was no change in the appearance of the varnish, it was evaluated as "Good". If there was a change in the appearance, such as resin precipitation or separation, it was evaluated as "Poor".

[0161] (Glass transition temperature (Tg)) The outer copper foil of the copper-clad laminate-I was entirely etched, and the Tg of the obtained sample was measured using a viscoelasticity spectrometer "DMS100" manufactured by Seiko Instruments Inc. Dynamic viscoelasticity measurement (DMA) was performed with a tensile module at a frequency of 10 Hz, and the temperature at which tan δ was maximized when the temperature was raised from room temperature to 300°C at a heating rate of 5°C / min was defined as Tg.

[0162] (Coefficient of Thermal Expansion (CTE)) The copper foil of the copper foil laminate-I was removed and used as a test piece, and the thermal expansion coefficient in the substrate surface direction (tensile direction, Y direction) at a temperature below the glass transition temperature of the cured resin was measured by the TMA method (Thermo-mechanical analysis). Specifically, a TMA device ("TMA6000" manufactured by SII Nano Technology Co., Ltd.) was used for the measurement in tensile mode. In order to eliminate the influence of thermal distortion of the test piece, the heating-cooling cycle was repeated twice, and the average thermal expansion coefficient from 40℃ to 100℃ on the second temperature displacement chart was measured. The smaller the value, the more favorable the result. The unit is ppm / ℃. [Measurement conditions] 1st cycle: Temperature rise range 30℃→Tg+10℃ 2nd cycle: Temperature rise range 30℃→300℃ Heating rate: 10℃ / min, Load: 1g Test piece: 3.5mm (width), 20mm (tensile direction)

[0163] (Copper foil adhesive strength) In the copper foil-clad laminate-I, the peel strength of the copper foil from the insulating layer was measured in accordance with JIS C 6481. A pattern 10 mm wide and 100 mm long was formed, and the copper foil was peeled off at a speed of 50 mm / min using a tensile tester, and the peel strength (peel strength) at that time was measured, and the obtained copper foil peel strength was taken as the copper foil adhesion strength. The measurement unit was kN / m.

[0164] (Dielectric properties: relative permittivity (Dk) and dielectric tangent (Df)) The copper foil was removed from the copper-clad laminate-III and the laminate was used as a test piece. The test piece was placed in a dryer at 105 degrees for 2 hours to remove the moisture in the test piece. The test piece was taken out of the dryer and placed in a desiccator to return it to 25 degrees, and the relative dielectric constant (Dk) and dielectric loss tangent (Df) of the test piece were measured by the cavity resonator perturbation method. Specifically, the relative dielectric constant (Dk) and dielectric loss tangent (Df-I) of the test piece at 10 GHz were measured using a network analyzer (N5230A manufactured by Agilent Technologies, Inc.).

[0165] (Dielectric properties: Change in Df after water absorption (ΔDf)) The dielectric loss tangent test piece was immersed in water at 23°C for 24 hours, and the surface water was wiped off. The dielectric loss tangent (Df-II) of the evaluation board at 10 GHz was measured in the same manner as above. ΔDf was calculated using the following formula, and the evaluation was based on the following criteria. ΔDf = (Df-II) - (Df-I) ◎: The change is less than 0.0025 ○: The change is 0.0025 or more and less than 0.0030 △: The change is 0.0030 or more and less than 0.0035 ×: The change is 0.0035 or more.

[0166] (Water absorption rate) The copper foil was removed from the copper-clad laminate-III, and the laminate was used as an evaluation board to evaluate the water absorption rate according to IPC-TM-650 2.6.2.1. The water absorption conditions were pretreatment at 105°C for 24 hours + constant temperature water treatment at 23°C for 24 hours. The water absorption rate was calculated based on the following formula. Water absorption rate (%) = ((mass after water absorption - mass before water absorption) / mass before water absorption) x 100

[0167] (Resin flowability) Resin flowability was evaluated using the above prepreg-II. The resin flowability of the prepreg-II obtained using the resin varnishes of Examples 1 to 9 was measured in accordance with IPC-TM-650 2.3.17D. The molding conditions were a temperature of 171°C and a pressure of 14 kgf / cm. 2 The prepreg was hot-pressed for 15 minutes. The number of prepregs used for the measurement was four of the prepreg-II prepared as described above.

[0168] (Circuit filling, grid pattern (remaining copper rate) 50%) One of the prepregs I mentioned above was used as a pressure body with 35 μm thick copper foil ("GTHMP35" manufactured by Furukawa Electric Co., Ltd.) placed on both sides. The temperature was 220°C and the pressure was 40 kg / cm. 2 The mixture was heated and pressed for 90 minutes under the above conditions to obtain a copper-clad laminate having copper foil attached to both sides and a thickness of 0.1 mm.

[0169] Then, a grid pattern was formed on the copper foil on both sides of the copper-clad laminate so that the copper remaining ratio was 50%, to form a circuit. On both sides of the board on which this circuit was formed, one prepreg-II was laminated, and a copper foil with a thickness of 12 μm ("GTHMP12" manufactured by Furukawa Electric Co., Ltd.) was placed to serve as a pressure body, and heating and pressing were performed under the same conditions as when the copper-clad laminate was manufactured. Thereafter, the outer layer copper foil was etched over the entire surface to obtain a sample. In this formed laminate (evaluation laminate), if the resin composition derived from the prepreg was sufficiently infiltrated between the circuits and no voids were formed, it was evaluated as "○". In addition, if the resin composition derived from the prepreg was not sufficiently infiltrated between the circuits and voids were formed, it was evaluated as "×". The voids can be visually confirmed.

[0170] (Handling and powder fall tests) When handling the prepreg, such as when producing or cutting the prepreg, powder of the resin composition or the semi-cured product thereof may fall off from the prepreg. That is, powder falling may occur. In this evaluation test, when the prepreg-II was cut with a cutter knife, if no powder falling was observed, it was evaluated as "○", and if powder falling was observed, it was evaluated as "×".

[0171] (Appearance of CCL after copper foil etching) The copper foil of the copper foil laminate-I was removed by etching, and the laminate was visually inspected for voids and scratches, and evaluated. Evaluation criteria: ○: No voids or blurs ×: Voids, scratches, and resin bleeding are observed on the surface of the 300x300mm laminate.

[0172] (Package warpage (μm)) First, a simple FC-mounted PKG (size 16mm x 16mm) was manufactured to measure the amount of PKG warpage by bonding and mounting a flip chip (FC) on a substrate using a stiffener ("HCV5313HS" manufactured by Panasonic Corporation). Here, the FC used was a Si chip with a size of 15.06mm x 15.06mm x 0.1mm and 4356 solder balls (height 80μm) mounted thereon. The substrate used was the copper-clad laminate-I from which the copper foil had been removed.

[0173] Next, the warpage of the FC mounted PKG was measured based on the shadow moire measurement theory using a warpage measurement device (AKROMETRIX's "THERMOIRE PS200"). The PKG warpage was calculated as the difference between the maximum and minimum warpage when the FC mounted PKG was heated from 25°C to 260°C and then cooled to 25°C.

[0174] The results are shown in Tables 1 to 3.

[0175] [Table 1]

[0176] [Table 2]

[0177] [Table 3]

[0178] (Consideration) As is clear from the results shown in Tables 1 to 3, it was shown that the present invention can provide a resin composition having low dielectric properties (Dk: 3.3 or less, Df: 0.0029 or less), as well as a high Tg and excellent adhesion (Tg 240°C or more, peel 0.45 kN / m or more) in the cured product. It was also confirmed that the use of the resin composition of the present invention can suppress the change in Df even after water absorption. Furthermore, it was confirmed that in all of the examples, the coefficient of thermal expansion (CTE) in the in-plane direction can be suppressed to a low level, and warping can be suppressed when the laminate is used as a package substrate. In addition, the handling and moldability of the prepreg and the appearance after etching of the CCL were also excellent.

[0179] In particular, it was found that by setting the content of the styrene-butadiene copolymer and the content ratio of each component within preferred ranges, a cured product with superior properties as described above could be obtained (Examples 1 to 12).

[0180] In contrast, in Comparative Example 1, which did not use styrene-butadiene copolymer, the thermal expansion coefficient was high, and sufficient low dielectric properties (especially Df) and low water absorption were not obtained, and the change in Df after water absorption was also large. The same results were obtained when a reaction initiator was added to Comparative Example 1 (Comparative Example 2).

[0181] Moreover, in Comparative Example 3 in which no maleimide compound was used, a high Tg was not obtained, and the CTE also became large.

[0182] In Comparative Example 4, in which a styrene polymer of a high molecular weight elastomer was used instead of a styrene-butadiene copolymer, a varnish could not be prepared as described above. In Comparative Example 5, a resin varnish of a MEK-toluene mixed solution could be obtained, but the resin varnish had poor storage stability. In addition, the prepared prepreg had low resin flowability and insufficient circuit filling. In addition, the resins did not mix well due to the large molecular weight, and bled, resulting in a poor appearance after copper foil etching of the CCL.

[0183] In Comparative Example 6, in which a low molecular weight styrene-based polymer was used instead of a styrene-butadiene copolymer, the Tg and adhesion were decreased, raising concerns about the connection reliability at high temperatures when used in a wiring board, and the thermal expansion coefficient of the laminate was increased, resulting in significant package warpage.

[0184] Furthermore, in Comparative Example 7, in which an unmodified polyphenylene ether compound was used, the curing of the resin composition did not proceed sufficiently, Tg decreased, and the adhesion, dielectric properties, and ΔDf were also poor.

[0185] This application is based on Japanese Patent Application No. 2019-177944, filed on September 27, 2019, the contents of which are incorporated herein by reference.

[0186] In order to express the present invention, the present invention has been described appropriately and sufficiently through the embodiments with reference to specific examples and drawings, etc., but it should be recognized that those skilled in the art can easily change and / or improve the above-mentioned embodiments. Therefore, unless the changes or improvements made by those skilled in the art are at a level that departs from the scope of the claims described in the claims, the changes or improvements are interpreted as being included in the scope of the claims. [Industrial Applicability]

[0187] The present invention has wide industrial applicability in technical fields related to electronic materials and various devices using the same.

Claims

1. A modified polyphenylene ether compound having a carbon-carbon unsaturated double bond at a molecular terminal; a maleimide compound having two or more N-substituted maleimide groups in one molecule, the maleimide groups having a functional group equivalent of 230 to 400 g / eq.; A liquid styrene-butadiene copolymer having a weight average molecular weight of less than 10,000 and having a 1,2-vinyl group; The modified polyphenylene ether compound has at least one structure represented by the following formula (1) or (2): the content ratio of the modified polyphenylene ether compound to the maleimide compound is 95:5 to 40:60; The resin composition has a content of the styrene-butadiene copolymer of 5 to 50 parts by mass per 100 parts by mass of the total of the modified polyphenylene ether compound, the maleimide compound, and the styrene-butadiene copolymer. 【Chemistry 1】 【Chemistry 2】 (In formulas (1) and (2), R 1 ~R 8 and R 9 ~R 16 each independently represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group. In addition, in the formulas (1) and (2), A and B are structures represented by the following formulas (3) and (4), respectively: 【Chemistry 3】 【Chemistry 4】 (In formulas (3) and (4), m and n each represent an integer of 1 to 50. R 17 ~R 20 and R 21 ~R 24 each independently represents a hydrogen atom or an alkyl group. Furthermore, in formula (2), Y is a structure represented by the following formula (5): 【Chemistry 5】 (In formula (5), R 25 and R 26 each independently represents a hydrogen atom or an alkyl group. Also, X 1 and X 2 each independently represents a substituent having a carbon-carbon unsaturated double bond represented by the following formula (6) or (7), 1 and X 2 may be the same or different. 【Chemistry 6】 In formula (6), a represents an integer of 0 to 10. Z represents an arylene group. 27 ~R 29 each independently represents a hydrogen atom or an alkyl group. 【Chemistry 7】 (In formula (7), R 30 represents a hydrogen atom or an alkyl group.

2. The resin composition according to claim 1, wherein the weight average molecular weight (Mw) of the modified polyphenylene ether compound is 1,000 to 5,000.

3. 3. The resin composition according to claim 1, wherein the styrene-butadiene copolymer has a styrene content of 50% by mass or less and a butadiene content of 50% by mass or more.

4. The resin composition according to claim 3, wherein the styrene-butadiene copolymer has a styrene content of 20 to 50% by mass and a butadiene content of 50 to 80% by mass.

5. The resin composition according to any one of claims 1 to 4, wherein the styrene-butadiene copolymer has a 1,2-vinyl content in butadiene of 30 to 70%.

6. A prepreg comprising the resin composition according to any one of claims 1 to 5 or a semi-cured product of the resin composition and a fibrous base material.

7. A resin-attached film comprising a resin layer containing the resin composition according to any one of claims 1 to 5 or a semi-cured product of the resin composition, and a support film.

8. A resin-coated metal foil comprising a resin layer comprising the resin composition according to any one of claims 1 to 5 or a semi-cured product of the resin composition, and a metal foil.

9. A metal-clad laminate having an insulating layer containing a cured product of the resin composition according to any one of claims 1 to 5 or a cured product of the prepreg according to claim 6, and a metal foil.

10. A wiring board having an insulating layer comprising a cured product of the resin composition according to any one of claims 1 to 5 or a cured product of the prepreg according to claim 6, and wiring.

Citation Information

Patent Citations

  • Pigment paste aid

    JP1981049773A

  • Modified polyphenylene ether resin, method of making the same and resin composition

    US20170190837A1

  • Resin composition for semiconductor package, and prepreg and metal clad laminate, which use same

    WO2018212459A1